Recent Developments in Vaccine Development for Viral Diseases: Zika, Ebola, and COVID-19 - Bang, Parisa (Journal of Neonatal Surgery, 2025)
Viral diseases pose significant threats to global health, often requiring rapid development of vaccines to mitigate outbreaks. The recent advancements in vaccine technologies, such as mRNA platforms, vector-based vaccines, and protein subunit vaccines, have revolutionized approaches to combating diseases like Zika, Ebola, and COVID-19. This paper reviews the scientific progress, challenges, and future directions in vaccine development for these diseases, emphasizing their unique epidemiological contexts and technological innovations